2006
DOI: 10.4067/s0716-97602006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cognition and memory: a reversible lesion with lidocaine into the anteromedial/posterior parietal cortex (AM/PPC) affects differently working and long-term memory on two foraging tasks

Abstract: Place memory is relevant for exploration and forage behaviour. When food supply is dispersed, a win-shift has advantage over a win-stay strategy. In the Olton Octagonal Maze, the rat follows a win-shift strategy using working memory. However, in the Olton 4x4 version, the rat follows a win-stay strategy, using both working and long-term memories. It has been suggested that the neocortex is required for the resolution of tasks demanding long-term, but not for that demanding working memory alone. The role of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In general, neuronal activity in PPC has been shown to correlate to a spectrum of behaviors, including motor behaviors that involve unrestricted exploration and motion/movement planning when subjects are head-fixed or navigate in a virtual reality setting (Espina-Marchant et al, 2006;Cui and Andersen, 2007;Harvey et al, 2012;Hauschild et al, 2012;Mimica et al, 2018;Crochet et al, 2019). We studied the functional architecture of PPC during tactile sensorimotor behavior in head-fixed rats, and the temporal dynamics of whisking and object touch resemble those observed in freely moving conditions (Carvell and Simons, 1990;Hobbs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In general, neuronal activity in PPC has been shown to correlate to a spectrum of behaviors, including motor behaviors that involve unrestricted exploration and motion/movement planning when subjects are head-fixed or navigate in a virtual reality setting (Espina-Marchant et al, 2006;Cui and Andersen, 2007;Harvey et al, 2012;Hauschild et al, 2012;Mimica et al, 2018;Crochet et al, 2019). We studied the functional architecture of PPC during tactile sensorimotor behavior in head-fixed rats, and the temporal dynamics of whisking and object touch resemble those observed in freely moving conditions (Carvell and Simons, 1990;Hobbs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the same lesion produced deficits in spatial learning; thus, the lesions were not without effect. Using two versions of a food foraging task, Espina-Marchant, Pinto-Hamuy, Bustamante, Morales, Robles, and Herrera-Marschitz (2006) examined the effects of temporarily inactivating the PPC with lidocaine during the delay period in a working memory procedure. The authors found that inactivating the PPC only had an effect when the task demands required both working memory and reliance on long-term memory, but not working memory alone.…”
Section: Working Memorymentioning
confidence: 99%
“…We have recently shown that the rat PPC is critical for performance of the TUNL task using temporary inactivations that lasted for the entire testing session 4 . Similarly, a number of previous studies show that the PPC is critical for visuospatial WM and memory‐guided perceptual decision making using visual stimuli 3,12,14,21 . In contrast, the PPC appears not to be necessary for WM tasks using odors or objects 18,32 .…”
Section: Discussionmentioning
confidence: 88%
“…The posterior parietal cortex (PPC) is an area of association cortex in the posterior cerebrum that is critical for a range of short‐term memory‐guided cognitive processes in primates and rodents including working memory (WM), 1‐12 perceptually guided decision making, 13 and sensory evidence accumulation 14,15 . Despite this evidence, however, the precise role of the rodent PPC in these cognitive processes is unclear.…”
Section: Introductionmentioning
confidence: 99%